TATA KELOLA TI BERBASIS COBIT 2019 PADA PT PETROSIDA GRESIK DENGAN KEMATANGAN TI BELUM OPTIMAL - M Rohid Nur Fajrian; Widyasari Puspa Permata Witra (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Information technology governance in a large-scale company needs to be supported by clear role structures, asset management, information systems, and control mechanisms. PT Petrosida Gresik has complex business processes across several directorates, yet its current IT governance practices are still not fully optimal. The main problems are reflected in asset recording that still relies on Excel, the absence of formal parameters for determining used-asset status, low user trust in iDempiere ERP data, weak budgeting control within the system, and unclear division of IT responsibilities in the organizational structure. The proposed solution is the design of IT governance based on COBIT 2019 to clarify processes, controls, roles, and evaluation mechanisms. This study used a descriptive qualitative method with a case study approach through document study, observation, and interviews. The results show that the relevant COBIT 2019 processes include EDM01, APO01, APO02, APO03, APO06, APO07, BAI09, DSS01, DSS06, dan MEA01. The proposed design includes gap mapping, RACI mapping, IT asset management procedures, centralized asset data, ERP validation, RKAP-based budget control, and strengthening of the IT organizational structure. The recommended structural changes include adding a Project Manager as a cross-directorate coordinator, strengthening the Information System and IT Governance Manager as the person responsible for systems, data, assets, security, and IT services, and dividing IT Department Staff into specific functions, namely information systems, database and ERP, network infrastructure, data security, IT assets, and helpdesk. This design is expected to improve accountability, data reliability, asset control, and IT alignment with organizational objectives.